The Moderating Role of Information Security Behaviour (ISB) on the Relationship between Digital Literacy (DL) and Information Security Culture (ISC): A Proposed Research Framework - Mohd Sharulnizam Kamarulzaman; Shamila Mohamed Shuhidan; Khalid Abdul Wahid (Proceedings, 2022)
Information Security Culture (ISC) has been suggested as a means of strengthening employees’ information security in the workplace. However, the role of employees and their digital skills in the process has been largely overlooked. Establishing an information security culture that strives to secure information by having employees who are digitally literate, as well as exerting influence on the employees’ behaviour regarding security, is one of the measures that may be utilised to mitigate risks provided by humans. Therefore, the purpose of this paper is to establish a research framework that moderates the effect of information security behaviour (ISB) on the relationship between digital literacy (DL) and information security culture (ISC). The study will improve DL and ISCB among employees who implement the country’s development plans, such as enhancing administrative functions, social infrastructure, and economic growth performance in accordance with MyDigital initiatives, as well as the government’s ISC.